Marginal and Internal Discrepancies Related to Margin Design of Ceramic Crowns Fabricated by a CAD/CAM System - Assuncao Souza, Rodrigo Othavio; Ozcan, Mutlu; Pavanelli, Carlos Augusto [UNESP]; Buso, Leonardo [UNESP]; Leao Lombardo, Geraldo Henrique [UNESP]; Araujo Michida, Silvia Masae [UNESP]; Melo Mesquita, Alfredo Mikail; Bottino, Marco Antonio (Wiley-Blackwell, 2012)
Purpose: The aim of this study was to evaluate the marginal discrepancy (MD) and internal discrepancy (ID) of ceramic crowns manufactured by a CAD/CAM system, having different finish lines. The hypotheses tested were that the finish line type would not influence the MD or ID of the crowns, and ID would not change in different regions.Materials and Methods: Three aluminum master dies (height: 5.5 mm, O: 7.5 mm, conicity: 6.) with different finish lines (TC: tilted chamfer; LC: large chamfer; RS: rounded shoulder) were manufactured. Ten impressions were made from each master die using a modified parallelometer. Impressions were poured in type IV dental stone, and 30 ceramic crowns (IPS Empress CAD, Ivoclar) were subsequently milled. The crowns were fixed on their respective metallic die using a metallic fixation device. The distance between the external edges of the crown to the edge of the cervical preparation was performed at 50 points on the respective metallic die (MD analysis). With the replica technique, the ID values of each crown were further evaluated at 12 points equidistant to each other in three regions: radius (R), axial (A), and occlusal (Occl). The measurements were performed using an optical microscope (250x). The data (mu m) were analyzed using ANOVA and Tukey's test (5%).Results: The RS group (28.24 +/- 11.42 mu m) showed significantly lower MD values (p = 0.001) than those of TC (99.92 +/- 18.32 mu m) and LC (64.71 +/- 25.64 mu m) groups, both of which also differed statistically from one another. The ID results demonstrated significantly lower values in the LC group (183.01 +/- 62.82 mu m) (p = 0.0014) than those of TC (216.26 +/- 83.23 mu m) and RS (219.12 +/- 87.24 mu m) groups. ID results of TC and RS were not significantly different. Additionally, the ID results showed significant differences among the regions (p = 0.0001). The null hypotheses were rejected.Conclusion: The RS finish line produced MD values significantly lower than tilted and large chamfer, but large chamfer presented the lowest internal discrepancy values. Independent of the finish line type, internal discrepancy was the lowest in the axial region followed by radius and occlusal regions.
Keywords: CAD; CAM system; internal discrepancy; marginal discrepancy